The role of psychopathic traits and moral disengagement in cyberbullying among adolescents. (13th December 2019) - Hoareau, Natacha; Bagès, Céline; Allaire, Mégane; Guerrien, Alain
Abstract: Background: The prevalence of cyberbullying suggests that about 15% of school‐aged children are involved in some way, although estimates vary widely. Preventing and limiting the behaviour will require more understanding of how mutable variables relate to it. There is some evidence linking higher psychopathy scores to cyberbullying, but the cognitive processes involved in 'moral disengagement' may provide better candidates for intervention. Aims: To test the hypothesis that psychopathy scores and moral disengagement ratings would each be associated with cyberbullying, but that sex and age would moderate any associations. Method: We conducted a cross‐sectional study with 334 11 to 15‐year‐olds (162 girls, 172 boys) from two French schools. Participants completed a self‐report questionnaire which measured cyberbullying, psychopathy traits and moral disengagement. Results: We found a significant relationship between moral disengagement scale scores and cyberbullying ratings, but a stronger relationship between psychopathy scores and likelihood of cyberbullying. Neither sex nor age of the students affected these relationships. Conclusion: This study adds to existing knowledge in showing that enduring personal qualities, as captured by a self‐rated psychopathy scale, may increase the risk of cyberbullying among adolescents. The findings suggest that teachers should be helped to monitor students' emotional and cognitive social skills and consider extra support for those who struggle to recognise or process others' distress.